The genus Oecetis McLachlan in Bolivia and northwestern Argentina (Trichoptera: Leptoceridae), with new species and identification key for males of Oecetis species from Mexico, Central and South America - Rueda Martin, Paola Alejandra (2011)
Six new species of Oecetis are described from Bolivia: O. carlibanezae, O. chipiriri, O. dominguezi, O. oberdorffi, O. pseudoamazonica and O. traini. Eight previously described species are recorded from Bolivia and northwestern Argentina: O. amazonica (Banks 1924), O. avara (Banks 1895), O. exisa Ulmer 1907, O. inconspicua (Walker 1852), O. knutsoni Flint 1981, O. paranensis Flint 1982a, O. punctipennis (Ulmer 1905) and O. rafaeli Flint 1991b. This work contains an identification key for males of Oecetis species from Mexico, Central and South America.